Evidences for gestures associated with pruritus in very young infants: a pilot study - Adrien Boyard; Camille Cosnard; David Simon; Camille Le Pors; Claire Abasq-Thomas; Marine Grandgeorge; Laurent Misery; Séverine Henry; Jean-Michel Roué (Scientific Reports)
Abstract The anatomical and functional basis for pruritus is present from birth. However, pruritus in this population is largely underestimated. The aim of this study was to analyze behaviors potentially associated with pruritus in infants under 6 months suffering from atopic dermatitis (AD). Infants under 6 months of age were enrolled in two arms: a healthy group and a group with moderate or severe AD. Infants were videotaped for at least 5 min and videos were analyzed by ethologists using the scan-sampling method. Thirty-four infants aged 2.5–5.5 months were included, 9 healthy infants and 25 infants with AD. Hand movements were more frequent in the AD group than in the healthy infants (p < 0.01). Video analysis revealed the presence of self-contact with grasping movements, which could be identified as immature scratching behavior. The statistical distribution of this behavior was greater in the AD group (p 0.03). Correlation analyses showed that this scratching behavior was associated with SCORAD (p 0.04), but not with age. This is the first study to highlight behaviors that can be identified in infants with pruritus before they develop the motor capacity to scratch.